Academic outcomes of multilingual children in Australia - Tarasuik, Joanne; O'Connor, Meredith; O'Connor, Elodie; Kvalsvig, Amanda; Goldfeld, Sharon; Gray, Sarah (My University, 2018)
Purpose: The Australian educational system is increasingly challenged to meet the needs of multilingual students, who comprise a fifth of the student population. Within the context of a monolingual English curriculum, multilingual children who enter school not yet English proficient may be at risk of experiencing inequitable educational outcomes. Method: We examined the relationship between the timing of multilingual children’s acquisition of receptive English vocabulary skills and subsequent reading and numeracy outcomes, as well as factors associated with earlier versus later timing of acquisition. Data were drawn from the Kindergarten-cohort (n¼4983) of the Longitudinal Study of Australian Children – a nationally representative, community sample of Australian children. Result: Linear regression analyses revealed that multilingual children who begin school with proficient receptive English vocabulary skills, or who acquire proficiency early in schooling, are indistinguishable from their monolingual peers in literacy and numeracy outcomes by 10–11 years. However, later acquisition of receptive English vocabulary skills (i.e. after 6–7 years) was associated with poorer literacy outcomes. In turn, socioeconomic disadvantage and broader language or learning problems predicted this later acquisition of receptive English vocabulary skills. Conclusion: All children need to be supported during the early years of school to reach their full educational potential.
Keywords: Culture -- Culturally and Linguistically Diverse; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Culture; Literacy and numeracy; Culturally and Linguistically Diverse; Learning, education and training